Health-promoting lecturing: development and validation of a measure - Vincent-Höper, Sylvie; Bogdanski, Jascha; Endrikat, Dunja; Janneck, Monique (Frontiers in Education, 2025)
IntroductionMental health impairments among university students have increased significantly in recent years. Although student mental health has received increasing attention, the role of university lecturers in shaping students’ well-being remains largely underexplored. Drawing on insights from occupational leadership research, it is assumed that lecturers play a key role in shaping the demands and resources of their students, which in turn impacts students’ health and well-being. Against this background, the present study systematically developed and validated a measure for assessing health-promoting lecturing behavior, referred to as the Inventory for Health-Promoting Lecturing (I-HeaL).MethodsAn online survey was conducted with a total sample of 1,715 students from German universities to assess the instrument’s psychometric properties. The instrument was first analyzed with an initial subsample (n1 = 300) and then cross-validated in a second subsample (n2 = 1,415).ResultsThe results indicate good overall psychometric quality, including satisfactory reliability coefficients across the subscales. Confirmatory factor analyses confirmed the proposed higher-order two-factor structure, differentiating between stressor- and resource-oriented lecturer behavior. Substantial correlations between lecturer behavior and various indicators of student health and well-being support the criterion validity of the measure.Discussion and conclusionComprising 15 subscales and 47 items, the developed instrument is a valid and reliable measure that allows for a differentiated assessment of lecturers’ behavior relevant to students’ health and well-being. In practice, it can serve as a basis for designing teaching and learning environments that foster student health and sustainable well-being in higher education.